(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Human beings are born to be physically active. Being physically active gives several advantages and is essential for a healthy life. Physical inactivity is to date one of the major risk factors for developing non-communicable diseases, which are responsible for nearly 70 of all deaths. It is well documented in the literature that daily physical activity reduces the risk of non-communicable diseases. The level of physical activity differs between regions of the world and between the countries. Moreover, there are age and gender differences.